If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4z + 2 = 5z + -8 Reorder the terms: 2 + 4z = 5z + -8 Reorder the terms: 2 + 4z = -8 + 5z Solving 2 + 4z = -8 + 5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-5z' to each side of the equation. 2 + 4z + -5z = -8 + 5z + -5z Combine like terms: 4z + -5z = -1z 2 + -1z = -8 + 5z + -5z Combine like terms: 5z + -5z = 0 2 + -1z = -8 + 0 2 + -1z = -8 Add '-2' to each side of the equation. 2 + -2 + -1z = -8 + -2 Combine like terms: 2 + -2 = 0 0 + -1z = -8 + -2 -1z = -8 + -2 Combine like terms: -8 + -2 = -10 -1z = -10 Divide each side by '-1'. z = 10 Simplifying z = 10
| y=x^3+3kx^3-9k^2x | | 3.56x+2= | | 3y/7=2y/5 | | 3*(6/5) | | -4m^2-23m+36=0 | | 3*6/5 | | 0.55x-12=18-0.55x | | 7x-(2x)= | | 14=s-s+2s+s-s | | 4*sin^2(x)+4*cos(x)=1 | | (2x-5)(4x^2-3x+1)= | | 6=6v-3v | | 2d-5=-8d+5 | | Y-80=1/14(x-5) | | -16=5v+-13v+-14v+6v | | f(-5)=2x | | (5/2x)-(7/4)=(3/4x) | | x+2xy-y=0 | | 7(x+6)=1(x-9) | | 15=14n-10n-3n | | 4x-28=6x+5 | | 5w+9.9=48+8w | | 17=7(4x-6)+3 | | 4x^2-13=13 | | 19=16t-13t-t-t-2t | | 8(7x-14)=504 | | x-3/4=3 | | 11=13y-12y-12y | | x+2=7+x+9 | | 16=12k-7k-k-4k+2k | | 8r+4=10x+2r | | 4x=-3x-28 |